Mikołaj Prokopowicz z Szadka – astrolog, astronom, historyk nauki, miłośnik i znawca książki (1489–1564) - Marszał, Tadeusz (Biuletyn Szadkowski, 2009)
Mikołaj was born in a middle-class family in Szadek. After completing studies at Cracow Academy started teaching at the Faculty of Philosophy in 1512. In 1515 he become professor of astrology and obtained the Chair of Astrology. In 1523 he was appointed to his first important administrative function at Cracow Academy, i.e. Dean of the Faculty of Philosophy. Later undertook studies at the Faculty of Theology, where he received doctorate in 1534. Soon afterwards he transferred to the Faculty of Theology. He was very strongly involved in university affairs and devoted much time and energy to administrative duties. In 1548 he became Rector of Cracow Academy, to hold this office for nine more terms (until 1561). Parallel with the university career he advanced in the Church hierarchy – in 1553 became the canon of the cathedral chapter in Cracow. His contribution to Polish literature includes official calendars and astrological forecasts (in Latin and Polish), published systematically in the period 1518–1531. Apart from astrology his other passion was reflected in the diary which he kept for many years. As the university library custodian, he devoted much energy to taking care of Cracow Academy’s collection of books. Mikołaj of Szadek had many disciples. He died in Cracow on 22 December 1564, having attained top level in university career and a high position in Church hierarchy.